2021
DOI: 10.1007/s12079-021-00658-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transcription factor B1 promotes the progression of hepatocellular carcinoma via enhancing aerobic glycolysis

Abstract: Mitochondrial dysfunctions play crucial roles in the carcinogenesis of various human cancers. However, the molecular mechanisms leading to mitochondrial dysfunction and thus cancer progression remains largely unclear. TFB1M (mitochondrial transcription factor B1) is a mitochondrial DNA-binding protein that activates the transcription of mitochondrial DNA. Our bioinformatics analysis indicated a significant up-regulation of TFB1M in hepatocellular carcinoma (HCC). Here, we investigated its clinical significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As for the TF family, a study reported by using the bioinformatic approach, that TFB1M was upregulated in tissue and HCC cells. This overexpression was related to poor survival, contributed to growth and metastasis, and promoted cell apoptosis, through impairment of oxidative phosphorylation, suggesting that dysregulation of TFB1M plays a crucial oncogenic role in HCC progression (Mu et al, 2022). Another study found in patients with Acute myeloid leukemia, that TFB1M , TFB2M , TFAM genes were upregulated, in which they were related to poor overall survival (Wu et al, 2019).…”
Section: Mitochondrial Rna Modifications and Its Enzyme Modifiers And...mentioning
confidence: 99%
“…As for the TF family, a study reported by using the bioinformatic approach, that TFB1M was upregulated in tissue and HCC cells. This overexpression was related to poor survival, contributed to growth and metastasis, and promoted cell apoptosis, through impairment of oxidative phosphorylation, suggesting that dysregulation of TFB1M plays a crucial oncogenic role in HCC progression (Mu et al, 2022). Another study found in patients with Acute myeloid leukemia, that TFB1M , TFB2M , TFAM genes were upregulated, in which they were related to poor overall survival (Wu et al, 2019).…”
Section: Mitochondrial Rna Modifications and Its Enzyme Modifiers And...mentioning
confidence: 99%
“…Although we did not find a difference in PER2 expression, PER2-regulated glycolytic genes, namely CDK1 , ENO1 , GAPDH , LDHA , and PGAM1 53 , all showed either a trend towards or a statistically significant mRNA expression elevation in KMT2D LOF cases compared to KMT2D WT cases, consistent with results demonstrated by Alam et al 53 in a Kmt2d knockdown mouse lung cancer cell line (Figure 4E; Supplementary Table S8; Methods). Furthermore, we found that, in addition to NDUFB5 , all GI tier I candidates in the STAD screen, namely ATP2B1 82 , DARS2 83 , MTG1 84 , NUBPL 85 , and TFB1M 68,69,86 (Supplemental Table S3), were SL interactors and were associated with mitochondrial and metabolic functions. Our results further support the notion that KMT2D may play a role in metabolism and that KMT2D LOF alterations in STAD cases may also confer a vulnerability to OXPHOS or glycolytic perturbations.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, FBXW11 is part of an E3 ubiquitin ligase complex involved in ubiquitination and proteasomal degradation in tumorigenesis signalling pathways 65 and has been shown to co-purify with the polycomb repressive complex 2 (PRC2) members EED 66 , SUZ12, and EZH2 65 , which play an antagonistic role to COMPASS complex members by depositing the repressive histone modification mark H3K27me3 67 . TFB1M is a mitochondrial transcription specificity factor that maintains homeostasis of oxidative phosphorylation and glycolysis 68,69 , pathways that have been shown to be dysregulated in KMT2D-deficient lung cancers 53 , epithelial cells, and Kabuki Syndrome patients 54 . Notably, KMT2D-deficient lung cancer cells depend on proper glycolytic activities for survival 53 , which is compatible with the notion that loss of TFB1M may be lethal for KMT2D-deficient cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation